Analisis Kemampuan Numerasi dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) Siswa Kelas VIII SMPN 134 Jakarta - Nurul Syafriah; Muhamad Sofian Hadi (Program Studi Pendidikan Matematika, 2023)
The Minimum Competency Assessment (AKM) is an assessment that designed to measure the literacy and numeracy abilities needed by all students to develop themselves and actively participate in society and to prepare students for the 21st century. The study aims to describe the numeracy ability of eighth graders of SMPN 134 Jakarta in answering the question of the Class Minimum Competency Assessment. The research technique used is a descriptive qualitative method. The research involved 58 eighth-grade students of SMPN 134 Jakarta during the 2022-2023 academic year who will be answering the question of the Class Minimum Competency Assessment on Phase D for numeracy competence. Furthermore, the results of students' work were categorized into three levels of numeracy ability, namely low, medium, and high. After being categorized, interviews were conducted with representatives of 3 students at each level of numeracy ability. Based on the results of study, it can be concluded that the numeracy ability level of eighth-grade students of SMPN 134 Jakarta is still low with details of 55 students at a low numeracy ability, 3 other students have medium numeracy ability, and no students at a high level of numeracy ability.